An analytical study of Buddhist symbols that appear in the Thai Yantra - เกิดแก้ว, ธีรโชติ (Journal of Buddhist Studies Chulalongkorn University, 2019)
Yanta means the shortening of Buddhist and other stories so that they are easily remembered and applied. The stories are presented through shapes, lines, images, characters, figures, incantations, story titles, and other elements which developed from mystical incantation scriptures of Brahmanism and Mantrayana Buddhism, together with other local faiths, to form the identity of the Thai Yanta lity since the Suvarnabhumi era. Thai Yanta is mostly geometrical in form, i.e., spherical, triangular, rectangular, and various other free forms. The purpose of their application can be divided into two categories: white magic with positive powers such as for defense and fortune, and black magic with negative powers such as for destruction or creating feelings of infatuation in others.